Language and Computers - Glass, Lelia; Dickinson, Markus; Brew, Chris; Meurers, Detmar (Language Science Press, 2024)
This book offers an accessible introduction to the ways that language is processed and produced by computers, a field that has recently exploded in interest. The book covers writing systems, tools to help people write, computer-assisted language learning, the multidisciplinary study of text as data, text classification, information retrieval, machine translation, and dialog. Throughout, we emphasize insights from linguistics along with the ethical and social consequences of emerging technology. This book welcomes students from diverse intellectual backgrounds to learn new technical tools and to appreciate rich language data, thus widening the bridge between linguistics and computer science.